History of insulin treatment of pediatric patients with diabetes in Korea - Jae Hyun Kim; Choong Ho Shin; Sei Won Yang (Korean Society of Pediatric Endocrinology, 2021)
The year 2021 is the centennial of insulin discovery. The discovery of insulin changes diabetes mellitus from a death sentence to a manageable disease. It became a historical turning point in the lives of people with diabetes. Since the first use of insulin in a patient in 1922, insulin and its analogs have been remarkable in saving the lives of people with diabetes. As insulin began to be used as a drug, it was introduced to, and used in Korea until now. This review briefly summarizes the history of insulin treatment in Korean children and adolescents with diabetes.